The Durability of Quantitative Host Resistance and Variability in Pathogen Virulence in the Interaction Between European Grapevine Cultivars and Plasmopara viticola - Heyman, Lisa; Höfle, Rebecca; Kicherer, Anna; Trapp, Oliver; Ait Barka, Essaid; Töpfer, Reinhard; Höfte, Monica (Frontiers in Agronomy, 2021)
European grapevine, Vitis vinifera, carries no major resistances against Plasmopara viticola, the causal agent of grapevine downy mildew. The introgression of quantitative trait loci conferring resistance to P. viticola (Rpv) from American and Asian donor species has resulted in a range of resistant cultivars. In light of the perennial nature of grapevine and the high evolutionary potential of P. viticola, the durability of this quantitative resistance is an important challenge. Durability of host resistance and variability in pathogen virulence may be evaluated by describing interactions between pathogen isolates and grapevine cultivars in terms of Rpv loci. A set of 16 cultivars carrying different combinations of Rpv loci, was challenged with five P. viticola isolates, obtained from susceptible or Rpv3.1+ V. vinifera cultivars. Based on the severity of sporulation, different host and pathogen phenotypes might be distinguished, which could be related to the presence of different Rpv loci. The hormonal responses before and during some interactions were compared to assess the resistance mechanisms underlying Rpv3.1, Rpv10, and Rpv12 and the infection mechanisms of the different isolates. This paper reports on the strength of some of the commonly used Rpv loci, single or stacked. Isolates derived from Rpv3.1+ hosts were able to sporulate intensely on cultivars carrying Rpv3.1, without triggering necrosis. Moreover, Rpv10 was not able to efficiently halt the development of the Rpv3.1-breaking isolate GPHPv1. Cultivars carrying Rpv12, however, were resistant to all five P. viticola isolates. Phytohormones might be implicated in the basal resistance against this pathogen, but during the early defense response, no significant hormonal responses to the isolates were observed. The isolate-specificity of the Rpv3- and Rpv10-mediated resistance suggests that these loci do not result in the most sustainable resistance. Furthermore, the isolate-specific behavior of the pathogen emphasizes the need for a characterization system for P. viticola. A standardized phenotyping assay may be used to determine P. viticola pathogen phenotypes or measure the durability, strength, and isolate-specificity of the host quantitative resistances. The characterization of both components of the pathosystem may lead to an increased understanding of the resistance mechanisms, beneficial for a durable deployment of resistance genes.